2017
DOI: 10.1007/s10753-017-0688-0
|View full text |Cite
|
Sign up to set email alerts
|

RX-207, a Small Molecule Inhibitor of Protein Interaction with Glycosaminoglycans (SMIGs), Reduces Experimentally Induced Inflammation and Increases Survival Rate in Cecal Ligation and Puncture (CLP)-Induced Sepsis

Abstract: The fused quinazolinone derivative, RX-207, is chemically and functionally related to small molecule inhibitors of protein binding to glycosaminoglycans (SMIGs). Composed of a planar aromatic amine scaffold, it inhibits protein binding to glycosaminoglycans (GAGs). RX-207 reduced neutrophil migration in thioglycollate-induced peritonitis (37%), inhibited carrageenan-induced paw edema (32%) and cerulein-induced pancreatitis (28%), and increased animal survival in the mouse model of cecal ligation and puncture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Extending the investigations into endogenously produced pro-resolving lipid mediators, Ramon et al not only identified PCTR1, a member of the protectin family as a potent monocyte/macrophage agonist but also established the therapeutic potential of PCTR1 supplementation in resolving inflammation using microbial-induced peritonitis in mice [70]. Similarly, Juhas et al confirmed the ability of RX-207 to reduce neutrophil migration using thioglycollate-induced peritonitis [71]. These examples not only underscore the importance of developing a mathematical model based on experimental data from mouse peritonitis, but also provide the rationale and future application of such a model for evaluating and predicting outcomes to be validated by subsequent experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Extending the investigations into endogenously produced pro-resolving lipid mediators, Ramon et al not only identified PCTR1, a member of the protectin family as a potent monocyte/macrophage agonist but also established the therapeutic potential of PCTR1 supplementation in resolving inflammation using microbial-induced peritonitis in mice [70]. Similarly, Juhas et al confirmed the ability of RX-207 to reduce neutrophil migration using thioglycollate-induced peritonitis [71]. These examples not only underscore the importance of developing a mathematical model based on experimental data from mouse peritonitis, but also provide the rationale and future application of such a model for evaluating and predicting outcomes to be validated by subsequent experimentation.…”
Section: Discussionmentioning
confidence: 99%